Repeatability of a piezoelectric force platform to measure impact metrics for a single model of football - Mills, K. L.; Billingham, J.; Choppin, S. (Sports Engineering, 2022)
The visco-elastic properties of a football influence how it bounces and therefore its performance in a game. Previously, high-speed camera footage has been used to quantify deformation, coefficient of restitution and contact time for an impact between a football and a rigid surface but these systems do not provide any information on the forces acting on the football during the impact. The aim of this study was to determine the repeatability of measuring the peak impact force, impulse, rise time and loading rate for four samples of the same model of football using a commercial force platform (Kistler 9281EA). A football impacted the floor-mounted piezoelectric-type force platform at 6.04 and 19.4ms-1. High absolute (coefficient of variation (CV) = 10%) and relative (intraclass correlation coefficient (ICC) = 0.94) repeatability was observed for repeated impacts at both velocities. The minimal detectable differences were calculated to evaluate the ability for the force platform to be used to make meaningful comparisons between footballs. For all metrics, the minimum detectable difference accounted for less than 5% of the mean value. Therefore, it can be concluded that provided the difference in impact metrics between football models exceeds the minimal detectable difference, the commercial force platform can be used to measure and detect differences in physical impact metrics between models of footballs.